Dynamics of characteristics of respiratory function for the development of coronary heart disease in patients with chronic obstructive lung disease - D. A. Vishnyak; M. A. Popova (SINAPS LLC, 2019)
Chronic obstructive pulmonary disease (COPD), along with cardiovascular disease, belongs to the leading chronic non-infectious diseases of our time, which, occurring in comorbidity, lead to the development of severe mutually aggravating complications.Objective: to determine the methods of diagnosis and prevention of coronary accidents in patients with COPD living in the northern latitudes, based on the dynamic assessment of the parameters of respiratory function.Materials and methods. The study was a holding during the five years extended instrumental examination (bodypletizmography methods, echocardiography) 182 patients with COPD (mean age of 65,0±1,2 years). Coronary events during prospective followup were recorded in 66 patients (mean age 65,0±1,2 years). Coronary events during prospective follow-up were recorded in 66 patients (mean age 65,0±1,2 years).Results: in a cohort of 976 patients with COPD, the number of patients with moderate severity (54%) was 6 times higher than the number of patients with extremely severe bronchial obstruction (8,6%) (p <0,001). During the five-year period in patients with isolated COPD (n=116) progression of violations of volume and speed indicators of external respiration function was registered. It should be noted that the course of COPD in this sample of patients was associated with a predominant decrease in restrictive indicators, manifested in the form of a decrease in the reserve volume of exhalation (RVE) by 20,6% (p=0,004) in patients with COPD, constituting a risk group for the development of coronary catastrophes, there was no significant dynamics of parameters of respiratory function for five years (p >0,05). Patients with lower values of volume parameters of external respiration function, such as RVE, inhalation capacity (IC), during the five-year follow-up period had a recorded coronary event (p <0,05). The greatest number of coronary accidents among patients with COPD of moderate and high risk was recorded in the first 3 years of follow - up, among patients of very high risk-evenly over 5 years. Coronary catastrophes were associated with periods of exacerbation of the underlying disease (p <0,05). Their frequency (myocardial infarction, angina, coronary death) for five years in patients with COPD with very high, high and moderate coronary risk was 33,9%, 10,5%, 1,52%, respectively. Using stepwise discriminant analysis, it was found that the leading prognostic markers of coronary accidents in patients with COPD living in the Northern latitudes, are the data of echocardiography (end-diastolic dimensions of the left ventricle, systolic pulmonary artery pressure) and bodypletizmography methods (RVE).Conclusion. It is recommended that the bodypletizmography methods and echocardiographic study all patients with COPD as binding studies to identify latent leaky restrictive disorders of function of external respiration with the first stage of the disease. Given the low level of diagnosis of COPD in Russia, a long asymptomatic course of the disease, the development of COPD after 10 years of living in the North, according to the literature, it is recommended to conduct an annual bodypletizmography as a screening method of examination of all smokers living in the Northern latitudes. Thus, the use of bodypletizmography with a targeted assessment of volume parameters, as well as echocardiographic studies, allows to identify groups at risk of coronary accidents and, thereby, to carry out timely prevention of the latter among patients with COPD.